2016
DOI: 10.1002/hbm.23505
|View full text |Cite
|
Sign up to set email alerts
|

Time course of gamma‐band oscillation associated with face processing in the inferior occipital gyrus and fusiform gyrus: A combined fMRI and MEG study

Abstract: Debate continues over whether the inferior occipital gyrus (IOG) or the fusiform gyrus (FG) represents the first stage of face processing and what role these brain regions play. We investigated this issue by combining functional magnetic resonance imaging (fMRI) and magnetoencephalography (MEG) in normal adults. Participants passively observed upright and inverted faces and houses. First, we identified the IOG and FG as face-specific regions using fMRI. We applied beamforming source reconstruction and time-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 63 publications
(101 reference statements)
1
22
0
Order By: Relevance
“…Several previous functional neuroimaging studies have reported that the FG is active during the observation of faces [e.g., Haxby et al, ; Sergent et al, ; for a review, see Kanwisher and Yovel, ]. Intracranial EEG [Engell and McCarthy, ; Klopp et al, ; Lachaux et al, ] and MEG [Uono et al, ] studies reported that this region exhibits gamma‐band activation in response to faces. However, the manner in which the FG may contribute to the functional network that includes the IOG and amygdala remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous functional neuroimaging studies have reported that the FG is active during the observation of faces [e.g., Haxby et al, ; Sergent et al, ; for a review, see Kanwisher and Yovel, ]. Intracranial EEG [Engell and McCarthy, ; Klopp et al, ; Lachaux et al, ] and MEG [Uono et al, ] studies reported that this region exhibits gamma‐band activation in response to faces. However, the manner in which the FG may contribute to the functional network that includes the IOG and amygdala remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that enhanced gamma oscillations are induced by faces over occipito-temporal areas when compared to control stimuli such as houses or scrambled stimuli (Zion-Golumbic and Zion-Golumbic et al, 2008;Gao et al, 2012). Since these oscillations show a physiological FIE (i.e., upright faces induced enhanced synchronization in gamma-band oscillations when compared to inverted faces), this activity likely reflects the difficulty of the visual system to bind facial features of inverted faces (i.e., holistic processing is not engaged by inverted stimuli) in a configural representation (Lachaux et al, 2005;Anaki et al, 2007;Dobel et al, 2011;Moratti et al, 2014;Matsuzaki et al, 2015;Uono et al, 2017). In line with behavioral results, even non-face stimuli (i.e., objects) show a physiological inversion effect, albeit of smaller magnitude (Tallon-Baudry and Bertrand, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In medial temporal lobe, parahippocampal gyrus is a gray matter layer around the hippocampus, which plays an important role in the encoding and extraction of memory ( Megevand et al, 2014 ). Additionally, olfactory region in parahippocampal gyrus is the gate linking to the hippocampus with rich incoming connections; fusiform gyrus is linked to the function including color information processing and the recognition of face, body, and word ( Uono et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%